Metode Pelatihan Dakwah Dalam Mewujudkan Keinginan Remaja Masjid Darus Sakinah Untuk Menjadi Da'i/Da'iah - Astri Anggraini Putri; Komaruddin Komaruddin; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This research is entitled Da'wah Training Methods in Realizing the Darus Sakinah Mosque Youth's Desire to Become Da'i/Da'iah. The aims of this study were (1) to find out the da'wah training methods in realizing the desire of young people at the Darus Sakinah Mosque to become Da'i/Da'iah, (2) to find out the supporting and inhibiting factors of da'wah training methods in realizing the desires of the Darus Sakinah Mosque youth to become Da'i/Da'iah. The research methodology used is qualitative, with research subjects consisting of 10 informants from the Darus Sakinah Mosque. Data collection techniques through observation, interviews and documentation. The results of the study show that (1) first, the preaching of Al-Hikmah teenagers are trained to understand that they must be clever in choosing words in which the words conveyed by the da'i must contain wisdom that is very much needed by da'wah so that the congregation is moved. Second, da'wah bil hal as an act of moving the assembly so that da'wah is more oriented towards the development of economic and social education in the community. Third, preaching Bil Oral preachers will be trained to use verbal skills and extensive knowledge needed so that later the implementation of da'wah can be easily understood by the congregation. Fourth, preaching kitabah as preaching that uses writing, whether in the form of using arguments, for example, prospective preachers will be trained to be good at writing verses of the Qur'an so that the steps to become preachers/da'iahs are maximized. (2) Factors supporting the first da'wah method, there is support from various parties, especially the DKM board who provide input and constructive criticism both related to da'wah training activities to the material that will be studied by teenagers. Second, there was support from Gema Hikmah, a da'wah training organization from Rambutan District which was organized to form competition activities starting from the Mosque Youth Communication Forum (FKRM) of Rambutan District, Banyuasin Regency. While the inhibiting factor, namely limited funds, is very important in every organization to carry out an activity.